Enhancing Qur’anic and Hadith Understanding Through Differentiated Instruction Model at MIS DDI Panggalo - Mardiana; Suci Nurzain (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) aims to enhance students’ understanding of the Qur’an and Hadith at MIS DDI Panggalo by applying the Differentiated Instruction Model. The study focuses on addressing the varying learning needs of students by providing tailored instructional methods, activities, and assessments that match their individual learning profiles. The research is conducted in two cycles, each consisting of planning, action, observation, and reflection stages. Data is collected through classroom observations, student assessments, and teacher reflections. The findings indicate that the Differentiated Instruction Model significantly improves students’ comprehension of Qur’anic verses and Hadith. By offering flexible learning paths based on students’ readiness, interests, and learning styles, students become more engaged in the learning process. The personalized approach allows students to understand complex religious texts at their own pace, fostering a deeper connection to the material. Teachers observed a marked increase in student participation, with students demonstrating improved ability to discuss and explain Qur’anic principles and Hadith teachings. Additionally, the study reveals that Differentiated Instruction promotes a positive classroom environment, where students feel more confident and motivated. By accommodating diverse learning needs, the model encourages a supportive and inclusive atmosphere, which enhances students’ academic performance and spiritual development. This approach also facilitates better classroom dynamics, as students work collaboratively, learning from one another’s strengths. Overall, the research concludes that applying the Differentiated Instruction Model in teaching the Qur’an and Hadith at MIS DDI Panggalo is effective in improving student engagement, comprehension, and retention of Islamic teachings. It provides valuable insights for educators seeking to implement flexible and inclusive teaching methods in religious education.